The problem of national thought in Iraq Until 1963 - Khalaf Kazem –, Rahim; Abdul Amir Mohsen, Hala (Journal of College of Education, 2022)
The beginnings of Arab nationalist thought appeared at the end of the nineteenth century and the beginning of the twentieth century, when Arab nationalism became the first political force that moved the masses in the Levant and Iraq - and it is worth noting that this Arab thought was the one who ruled the Levant and Iraq after the First World War, after that  Sharif Hussein announced the Great Arab Revolt in 1916 AD, which adopted the Arab nationalist thought in its confrontation with the Ottoman Caliphate and the policy of Turkification pursued by the Assembly of Union and Progress with all the nationalities under the banner of the Ottoman Empire, including Arab nationalism, and this national problem was cast on the establishment of the Iraqi state in 1921 AD because  Subordination of Iraq to the Ottoman Empire for several centuries.  This research was divided into an introduction, four axes, and a conclusion.  The First Republican 1958 AD - 1963 AD.The research relied on several sources, including the book “Republican Iraq” by researcher Majid Khadduri, Laith Al-Zubaidi’s book “The July 14, 1958 A.D. Revolution in Iraq,” and the book “The Iraqi State between Nationalist Orientation and British Propaganda 1921-1958AD” by researcher Fawaz Hammad Mahmoud Al-Ithawi
Keywords: ideas, nationalism, conflicts, problematic, procedures